Culture Media Based on Leaf Strips/Root Segments Create Compatible Host/Organ Setup for in vitro Cultivation of Plant Microbiota - Nemr, Rahma A.; Patz, Sascha; Abdelwakeel, Saad M.; Khalil, Mohab; Ben Djadid, Ali; Abdelfadeel, Mohamed R.; Morsi, Ahmed T.; Goda, Hanan A.; Youssef, Hanan H.; Hamza, Mervat; Abbas, Mohamed; Fayez, Mohamed; et al. (Frontiers in Sustainable Food Systems, 2021)
Plant microbiota have co-evolved with their associated plants in the entire holobiont, and their assemblages support diversity, health and productivity on our planet. Of importance is the in vitro cultivation and identification of their hub taxa for possible core microbiome modification. Therefore, we recently introduced the in situ-similis culturing strategy, based on the use of plant leaves as platform for in vitro growth of plant microbiota. Here, we augment the strategy by the incorporation of the Most Probable Number (MPN) method, based on the use of leaf strips and root segments immersed in plain semi-solid water agar, as growth milieu. Cultivability of bacterial endophytes of sunflower plants (Helianthus annuus L.) was monitored in terms of MPN population estimates, community composition through PCR-DGGE analysis and 16S rRNA gene sequencing of representative isolates. The method efficiently enriched the plant endophytes as MPN estimates exceeded log 7.0 g-1 leaf/root. Results of PCR-DGGE analyses indicated divergence in community composition of cultivable bacterial endophytes primarily attributed to the type of culture media, signaling a certain degree of plant-organ specificity and compatibility. Based on 16S rRNA gene sequencing of representative bacterial isolates, 20 genera comprising 32 species were enriched in leaf strips- and root segments-based media. They belonged to the three phyla Bacteroidetes, Firmicutes and Proteobacteria, especially Alpha- and Gammaproteobacteria. The MPN strategy furnished a diversified nutritive platform in terms of homologous/heterologous and ambient/limited oxygenic cultivation. As a result, cultivability was extended to more 8 genera - Bosea, Brevundimonas, Caulobacter, Chitinophaga, Pseudoxanthomonas, Scandinavium, Sphingobacterium, Starkeya - among them three genera, namely Caulobacter, Scandinavium and Starkeya, which were not yet reported for Sunflower, even with the use of metagenomics sequencing methods. Possible unknown species or even one new putative genus were enriched. Thus, not only potential members of the major microbiome but also the rare isolates of satellite microbiomes can be isolated using the presented in situ similis MPN-cultivation strategy. It is a feasible addition to traditional cultivation methods to probe deeper for both the major and rare taxa and fill the many cultivation gaps within plant microbiota.